PENDIDIKAN ISLAM MASA ORDE LAMA: PERAN ULAMA DAN TOKOH-TOKOH PENDIDIKAN ISLAM - Sangkot Hayati; Rahmad Setyawan; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
The aim of this research is to analyze the politics of Islamic education during the Old Order by highlighting the role of ulama and Islamic education figures. This research uses a historical approach and qualitative analysis of various historical documents. This study found that Islamic scholars and educational figures have a significant influence in the development of Islamic educational curricula and institutions. They play a role in integrating Islamic values ​​with the national curriculum as well as establishing and managing Islamic educational institutions, such as Islamic boarding schools and madrasas. Research findings show that despite various obstacles, the contribution of Islamic scholars and educational figures during the Old Order era provided an important foundation for the development of Islamic education in Indonesia. Their role in this period became the forerunner for the transformation of the Islamic education system in the next era.